Unveiling the Impact of E-Books on Elementary Students' Reading Com-prehension and Learning Achievement - Muhammad Irwan Syahputra; Gamar Al Haddar; Muhammad Riza Syahputra; Suherman Chandra (Institute of Computer Science (IOCS), 2024)
The digital age has ushered in a new era of educational possibilities, offering innovative tools and resources to engage students in the learning process. This research investigates the impact of e-books on elementary school students' reading comprehension, utilizing a mixed-methods approach to provide a comprehensive understanding of the subject. The study, conducted in a diverse urban elementary school, employed both quantitative pre- and post-assessments and qualitative interviews with students, teachers, and parents to assess the effects of e-book integration. Quantitative findings revealed a statistically significant improvement in students' reading comprehension scores following exposure to e-books. Qualitative insights highlighted enhanced engagement, motivation, and differentiated learning experiences. Educators, students, and the broader educational community stand to benefit from the results of this research, which provide evidence of the feasibility and benefits of e-book integration in elementary education. These findings offer promising prospects for the evolution of curriculum design, educational technology implementation, and more inclusive and accessible learning environments in the digital age.